Shape memory hydrogel
By using specific copolyester polymers and postpolymerization reaction methods in morphological memory hydrogels, the problem of difficult change in mechanical properties after polymerization is solved, and flexible adjustment of the mechanical properties of hydrogels and improvement of the performance of morphological memory hydrogels is achieved.
Patent Information
- Application Number
- JP2023164275
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing physical memory hydrogels are difficult to change their mechanical properties after polymerization, especially in the fields of medicine and beauty.
A hydrogel consisting of a specific copolyester polymer is employed, whose polymer matrix is formed by copolymerization of a representative unit and a vinyl unsaturated unit with a reactive function, and its mechanical properties are adjusted by postpolymerization reaction.
It realizes flexible adjustment of the mechanical properties of morphological memory hydrogels, maintains the excellent performance of morphological memory hydrogels, and enhances its applicability.
Smart Images

Figure 2025055002000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogel having a shape memory function. [Background technology]
[0002] Hydrogels, which consist of a three-dimensional polymer network structure, are essentially polymers with high affinity for water that are swollen in aqueous solvents. Hydrogels have biocompatibility, flexibility, transparency, and substance encapsulation capabilities due to their high water content, and are used in a wide range of fields from medicine to engineering.
[0003] On the other hand, since hydrogels are mostly composed of water, it is difficult to deform, fix, or memorize their shapes. The inventors have succeeded in developing a hydrogel that memorizes its initial shape and can fix / recover its shape by thermal stimulation by utilizing the reversible hydrogen bonds of a chemically crosslinked thermoresponsive amino acid-derived vinyl polymer (Patent Document 1).
[0004] However, since the initial shape and intrinsic mechanical properties of this gel system are determined during polymerization, it is difficult to change the gel properties after polymerization. Controlling the mechanical properties (viscoelasticity) of the gel is particularly important for applications in the medical and cosmetic fields.
[0005] Research has begun into the dynamic behavior of changes in elastic modulus by using functional hydrogels whose elastic modulus can be actively controlled by external stimuli after polymerization (Non-Patent Document 1). For example, a hydrogel has been proposed in which the main network is polyethylene oxide and the crosslinking points have nitrobenzyl ether groups that cleave in response to light, and a dynamic hydrogel has been reported in which the elastic modulus decreases as the crosslinking points cleave in response to light irradiation (Non-Patent Document 2).
[0006] However, such techniques are not sufficient to control the mechanical properties of hydrogels freely. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 7025749 [Non-patent literature]
[0008] [Non-Patent Document 1] JA Burdick and WL Murphy, Nat. Commun., 3,1269(2012) [Non-Patent Document 2] AM Kloxin, AM Kasko, CN Salinas, and KSAnseth, Science, 324, 59(2009) Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made in consideration of these problems, and aims to overcome these issues with conventional shape-memory hydrogels and provide a new shape-memory hydrogel whose mechanical properties can be freely tuned through post-polymerization reactions. [Means for solving the problem]
[0010] The shape-memory hydrogel according to the present invention is a shape-memory hydrogel containing a polymer matrix and water, characterized in that the polymer matrix is a copolymer of a monomer represented by formula (1) and an ethylenically unsaturated monomer having a reactive functional group, where R1 is hydrogen or a linear or branched alkyl group having 1 to 6 carbon atoms.
[0011] [ka]
[0012] The polymer matrix can be represented as a copolymer represented by formula (2), where R2 is hydrogen or a linear or branched alkyl group having 1 to 6 carbon atoms, X is a structure in which a substituted or unsubstituted hydroxyl group, a substituted or unsubstituted amino group, a substituted or unsubstituted carboxyl group, a substituted or unsubstituted thiol group, a substituted or unsubstituted aldehyde group, a cyano group, or an epoxy group is bonded directly or via a linker, a is 1 to 20, and n is a repeating unit defined by the molecular weight of the compound.
[0013] [ka]
[0014] The linker is a structure containing an amide bond, an ether bond, an ester bond, a urethane bond, or a thioether bond.
[0015] Also, in formula (2), X represents -CONH-Q, -COO-Q, an alkylene group, or an arylene group, Q is CHR3COR4, R3 is selected from the group consisting of H, CH2OH, CH(OH)CH3, (CH2)4NH2, CH2COOR5, (CH2)2COOR5, CH2SH, CH2CONH2, and (CH2)2CONH2, R5 is selected from the group consisting of H, an alkyl, aralkyl, or aryl group having 1 to 9 carbon atoms, R4 is NH2 or OR6, and R6 can also be represented as H, an alkyl, aralkyl, or aryl group having 1 to 9 carbon atoms. Effect of the Invention
[0016] According to the present invention, a new shape-memory hydrogel can be obtained which maintains the properties of a shape-memory hydrogel and whose mechanical properties can be freely tuned by a post-polymerization reaction. [Brief description of the drawings]
[0017] [Figure 1]FIG. 1 shows the temperature response evaluation of P(NAGAm-NASMe) under dilute concentration conditions. [Diagram 2] FIG. 1 shows the storage modulus (G') of P(NAGAm-NASMe) post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde per unit. [Diagram 3] This figure shows the change in swelling ratio of P(NAGAm-NASMe), which was post-crosslinked with 1, 10, or 100 equivalents of the crosslinking agent glutaraldehyde per unit, when it was alternately immersed in water at 4°C and 25°C. [Figure 4] FIG. 1 shows the shape fixation rate (F) of P(NAGAm-NASMe) post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde per unit. [Diagram 5] FIG. 1 shows the shape recovery rate (R) of P(NAGAm-NASMe) post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde per unit. [Figure 6] FIG. 1 shows the storage modulus (G′) of P(NAGAm-NASMe) post-crosslinked with 10 equivalents of hexamethylene diisocyanate per unit. [Figure 7] FIG. 13 shows the storage modulus (G′) of P(NAGAm-NAG) post-crosslinked with 10 equivalents of ethylenediamine per unit. [Figure 8] FIG. 1 is a photograph showing the self-repairing properties of the hydrogel of the present invention. [Figure 9] FIG. 11 compares the tensile stress of the hydrogel before and after repair. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail with reference to the attached drawings. However, the embodiment is intended to facilitate understanding of the principles of the present invention, and the scope of the present invention is not limited to the embodiment described below. Other embodiments in which a person skilled in the art appropriately replaces the configuration of the embodiment described below are also included in the scope of the present invention.
[0019] 1. Shape-memory hydrogel The shape-memory hydrogel of the present invention contains a polymer matrix and water, and the polymer matrix is a copolymer of a monomer represented by formula (1) and an ethylenically unsaturated monomer having a reactive functional group.
[0020] [ka]
[0021] Here, R1 is hydrogen or a linear or branched alkyl group having 1 to 6 carbon atoms.
[0022] The polymer matrix can be described by a copolymer shown in formula (2).
[0023] [ka]
[0024] Here, R2 is hydrogen or a linear or branched alkyl group having 1 to 6 carbon atoms. X is a structure in which a substituted or unsubstituted hydroxyl group, a substituted or unsubstituted amino group, a substituted or unsubstituted carboxyl group, a substituted or unsubstituted thiol group, a substituted or unsubstituted aldehyde group, a cyano group, or an epoxy group is bonded directly or via a linker, a is 1 to 20, and n is a repeating unit defined by the molecular weight of the compound. a is 1 to 20, and n is a repeating unit defined by the molecular weight of the compound, and although not limited thereto, for example, n is 1,000 to 1,000,000.
[0025] Here, the "substituted" in "substituted or unsubstituted" is not particularly limited, and means, for example, substituted with one or more substituents selected from the group consisting of deuterium, a cyano group, a halogen group, a nitro group, a linear, branched or cyclic alkyl group having 1 to 24 carbon atoms, a halogenated linear, branched or cyclic alkyl group having 1 to 24 carbon atoms, an aryl group having 6 to 24 carbon atoms, an arylalkyl group having 7 to 24 carbon atoms, an alkylaryl group having 7 to 24 carbon atoms, a heteroaryl group having 2 to 24 carbon atoms, a heteroarylalkyl group having 2 to 24 carbon atoms, an alkylamino group having 1 to 24 carbon atoms, a diarylamino group having 12 to 24 carbon atoms, a diheteroarylamino group having 2 to 24 carbon atoms, an aryl(heteroaryl)amino group having 7 to 24 carbon atoms, an alkylsilyl group having 1 to 24 carbon atoms, and an arylsilyl group having 6 to 24 carbon atoms.
[0026] The linker is a structure containing an amide bond, an ether bond, an ester bond, a urethane bond, or a thioether bond.
[0027] In addition, in formula (2), X represents -CONH-Q, -COO-Q, an alkylene group, or an arylene group, Q is CHR3COR4, R3 is selected from the group consisting of H, CH2OH, CH(OH)CH3, (CH2)4NH2, CH2COOR5, (CH2)2COOR5, CH2SH, CH2CONH2, and (CH2)2CONH2, R5 is selected from the group consisting of H, an alkyl, aralkyl, or aryl group having 1 to 9 carbon atoms, R4 is NH2 or OR6, and R6 can also be H, an alkyl, aralkyl, or aryl group having 1 to 9 carbon atoms.
[0028] The ethylenically unsaturated monomer is not particularly limited, and may be, for example, acryloyl, methacryloyl, or vinyl.
[0029] Furthermore, the ethylenically unsaturated monomer is not particularly limited, and may be, for example, any one of N-(meth)acryloylserine methyl ester, N-(meth)acryloylglycine, N-(meth)acryloylvaline, N-(meth)acryloyllysine methyl ester, N-(meth)acryloylcysteine methyl ester, N-(meth)acryloylglutamic acid methyl ester, N-(meth)acryloylaspartic acid methyl ester, (meth)acryloylglycine amide, (meth)acryloylasparagine amide, or (meth)acryloylglutamine amide, and is preferably N-acryloylserine methyl ester shown below.
[0030] [ka]
[0031] Also preferred is N-acryloylglycine as shown below.
[0032] [ka]
[0033] Furthermore, the ethylenically unsaturated monomer is not particularly limited, and may be any one of acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, N-(2-hydroxyethyl)acrylamide, N-(2-aminoethyl)methacrylamide hydrochloride, maleic acid, monomethyl maleic acid, 2-carboxyethyl methacrylate, N,N' dimethylacrylamide, N,N' diethylacrylamide, butylcarbamoylethyl acrylate, itaconic acid, crotonic acid, fumaric acid, styrenesulfonic acid, vinylbenzoic acid, vinylphosphonic acid, sulfopropyl (meth)acrylate, and sulfatoethyl (meth)acrylate.
[0034] In the hydrogel of the present invention, the ratio of the polymer matrix content to the water content is not particularly limited, but for example, the polymer matrix content is preferably within the range of 3 to 50 parts by weight, more preferably within the range of 5 to 30 parts by weight, relative to 100 parts by weight of the total amount of the hydrogel. If the polymer matrix content is less than 3 parts by weight relative to 100 parts by weight of the total amount of the hydrogel, the shape retention of the hydrogel may be insufficient, and the hydrogel may be too soft or easily torn, and if it exceeds 50 parts by weight relative to 100 parts by weight of the total amount of the hydrogel, the hydrogel may become hard, losing its flexibility or losing its transparency.
[0035] The hydrogel of the present invention may contain a water-soluble polymer, if necessary. Usable water-soluble polymers are not particularly limited, but include, for example, a homopolymer of vinylpyrrolidone (i.e., polyvinylpyrrolidone); a vinylpyrrolidone copolymer such as a copolymer of vinyl alcohol and vinylpyrrolidone, a copolymer of ether-modified vinyl alcohol and vinylpyrrolidone, or a copolymer of vinylpyrrolidone and vinyl acetate; polyvinyl alcohol, polyacrylic acid, sodium polyacrylate, sodium carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, sodium alginate, dextran, various proteins, nucleic acids, etc.
[0036] Furthermore, to the hydrogel of the present invention, other medicinal components such as preservatives, bactericides, anti-rust agents, antioxidants, stabilizers, fragrances, surfactants, colorants, anti-inflammatory agents, vitamins, whitening agents, etc. may be appropriately added as necessary within the range that does not impair the effects of the present invention. These additives may be used alone or in combination of two or more kinds.
[0037] 2. Manufacturing method of shape-memory hydrogel The method for producing the hydrogel according to the present invention will be described below.
[0038] The hydrogel of the present invention can be produced by a production method in which the compound represented by formula (1) and an ethylenically unsaturated monomer having a reactive functional group are dissolved in a mixed solvent of water and DMSO, an initiator is added, and copolymerization is carried out. The blended liquid can contain the above-mentioned water-soluble polymer and various additives as necessary. The reaction temperature is not particularly limited as long as the copolymerization proceeds quickly, but is, for example, 50°C to 80°C.
[0039] [ka]
[0040] For example, N-acryloylglycinamide and N-acryloylserine methyl ester can be reacted by dissolving them in a mixed solvent of water and DMSO, adding an initiator and a crosslinking agent, and copolymerizing them according to the reaction formula shown in the following formula.
[0041] [ka]
[0042] For example, the reaction between N-acryloylglycine amide and N-acryloylglycine can be carried out by dissolving them in a mixed solvent of water and DMSO, adding an initiator, and copolymerizing them according to the reaction formula shown below.
[0043] [ka]
[0044] It is preferable that the above-mentioned mixture liquid contains a polymerization initiator. The polymerization initiator is not particularly limited, and examples thereof include a thermal polymerization initiator and a photopolymerization initiator.
[0045] The thermal polymerization initiator is not particularly limited as long as it is cleaved by heat to generate radicals, and examples thereof include organic peroxides such as benzoyl peroxide; azo-based polymerization initiators such as azobiscyanovaleric acid, azobisisobutyronitrile, azobisamidinopropane dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride; and persulfates such as potassium persulfate and ammonium persulfate. These thermal polymerization initiators may be used alone or in combination of two or more. In addition, a redox polymerization initiation system in which ammonium persulfate and tetramethylethylenediamine are combined may be used.
[0046] The photopolymerization initiator is not particularly limited as long as it is cleaved by ultraviolet or visible light to generate radicals, and examples thereof include azo-based polymerization initiators such as 2,2'-azobis-N-(2-hydroxyethyl)propionamide and 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, α-hydroxyketones, α-ketonecarboxylic acids, α-aminoketones, benzyl methyl ketal, bisacylphosphine oxides, metallocenes, etc. These photopolymerization initiators may be used alone or in combination of two or more.
[0047] The amount of the polymerization initiator used is preferably 0.01 to 1.0 parts by weight relative to 100 parts by weight of the total amount of monomers used in the production of the hydrogel (total amount of the above-mentioned mixed solution). If the amount of the polymerization initiator used is less than 0.01 parts by weight relative to 100 parts by weight of the total amount of monomers (total amount of the above-mentioned mixed solution), the polymerization reaction is not sufficiently promoted, and crosslinkable divinyl compounds and the like may remain in the obtained hydrogel, while if it is more than 1.0 part by weight, there is a risk that the polymerization initiator may remain in the obtained hydrogel or that it may be difficult to increase the molecular weight.
[0048] 3. How to use shape memory hydrogel The shape-memory hydrogel of the present invention can be post-crosslinked using a crosslinking agent, utilizing the covalent bonds between the polymers that form the polymer matrix.
[0049] The crosslinking agent used for the post-crosslinking is not particularly limited, and examples thereof include glutaraldehyde, hexamethylene diisocyanate, and ethylenediamine.
[0050] For example, P(NAGAm-NASMe) shown below can be post-crosslinked using glutaraldehyde. Glutaraldehyde is a bifunctional reagent with high crosslinking properties and is used in crosslinking reactions targeting hydroxyl groups and amino groups. Post-crosslinking targeting amino groups in polymers allows crosslinking between polymers under relatively mild conditions.
[0051] [ka]
[0052] The amount of the crosslinking agent used is not particularly limited, and for example, 1 to 100 equivalents of the crosslinking agent can be used per unit of the polymer. Depending on the type and amount of the crosslinking agent used, it becomes possible to freely tune the mechanical properties of the hydrogel by a post-polymerization reaction.
[0053] As a result, the hydrogel of the present invention is an extremely unique polymeric material that exhibits shape memory while maintaining the advantages of hydrogels (flexibility / transparency / substance encapsulation / biocompatibility, etc.) and furthermore, allows for free tuning of mechanical properties. Therefore, the hydrogel of the present invention can be suitably used as, for example, biomaterials, medical materials, cosmetics, quasi-drugs, industrial materials, and hobby materials. EXAMPLES
[0054] (1) Polymerization of P(NAGAm-NASMe) P(NAGAm-NASMe) was polymerized according to the scheme and reaction formula shown below. NAGAm (0.608 g, 4.75 mmol) and NASMe (0.0390 g, 0.250 mmol) were dissolved as monomers in a water / DMSO (11 / 4) mixed solvent, and the crosslinker PEGDA (0.000755 mL, 0.00250 mmol) and initiator APS (0.00647 g, 0.0283 mmol) were added to make the total volume 5 mL.
[0055] This solution was added to a polymerization tube, and freeze-degassing / nitrogen replacement was performed using liquid nitrogen as a refrigerant. The sealed polymerization tube was placed in an oil bath at 70°C for 18 hours for polymerization. After polymerization, the polymerization tube was removed from the oil bath and stopped with cold water. The resulting compound was purified using a dialysis membrane with a molecular weight cutoff of 25,000 Da, and freeze-dried to obtain the target polymer.
[0056] [ka]
[0057] (2) Polymerization of P(NAGAm-NAG) P(NAGAm-NAG) was polymerized according to the scheme and reaction formula shown below. NAGAm (0.608 g, 4.75 mmol) and NAG (0.0320 g, 0.250 mmol) were dissolved in a water / DMSO (11 / 4) mixed solvent, and APS (0.0064 g, 0.0283 mmol) was added to make the total volume 5 mL.
[0058] This solution was added to a polymerization tube, and freeze-degassed / nitrogen-substituted using liquid nitrogen as a refrigerant. The sealed polymerization tube was placed in an oil bath at 70°C for 18 hours for polymerization. After polymerization, the polymerization tube was removed from the oil bath and stopped with cold water. The resulting compound was purified using a dialysis membrane with a molecular weight cutoff of 25,000 Da, and freeze-dried to obtain the desired polymer.
[0059] [ka]
[0060] (3) Temperature responsiveness evaluation The temperature response of P(NAGAm-NASMe) was evaluated under dilute concentration conditions: polymer concentration 1 wt%, optical path length 1 cm, and heating / cooling rate 0.5°C / min.
[0061] Figure 1 shows the temperature response evaluation of P(NAGAm-NASMe) under dilute concentration conditions. As shown in Figure 1, P(NAGAm-NASMe) exhibited UCST-type temperature response behavior. Although not shown in the figure, P(NAGAm-NAG) also exhibited UCST-type temperature response behavior.
[0062] (4) Preparation of hydrogel Water was added to the polymerized P(NAGAm-NASMe) powder to a concentration of 4 wt%, and after dissolving it in a microwave oven (approximately 90°C), it was poured into a mold and cooled to 4°C to gel it.
[0063] Similarly, the polymerized P(NAGAm-NAG) powder was dissolved in water (approximately 90°C) in a microwave oven and then cooled to 4°C to cause it to gel.
[0064] (5) Post-polymerization crosslinking reaction with a crosslinking agent The gel for measurement was prepared by immersing the polymerized P(NAGAm-NASMe) in a 4 mL aqueous solution containing 1, 10, or 100 equivalents of the crosslinking agent glutaraldehyde per unit for 1 hour to carry out a post-crosslinking reaction.
[0065] (6) Evaluation of mechanical strength Dynamic viscoelasticity measurements were performed on P(NAGAm-NASMe) that had been post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde, and the storage modulus (G') at 6.3 rad / s was compared. The measurement conditions were 4°C and 1% strain. Figure 2 shows the storage modulus (G') of P(NAGAm-NASMe) that had been post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde per unit. As shown in Figure 2, it was revealed that the storage modulus (G') can be controlled by the degree of crosslinking. When crosslinking was performed with 10 equivalents of glutaraldehyde per unit, it is believed that the crosslink density increased, and the storage modulus (G') increased.
[0066] (7) Evaluation of swelling-shrinkage behavior The swelling-shrinking behavior of P(NAGAm-NASMe) post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde was evaluated. P(NAGAm-NASMe) post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde was molded into 1 cm squares and 1 mm thick pieces. The molded hydrogels were immersed in pure water at 4°C for 24 hours, then alternately immersed in water at 4°C and 25°C for 1 hour, and the weight (W S After the measurement, the weight (W D ) was measured again and the swelling percentage (%) was calculated.
[0067] The swelling ratio was calculated according to the following formula.
[0068] Swelling percentage (%) = {(W S -W D ) / W D} × 100
[0069] Figure 3 shows the change in swelling ratio of P(NAGAm-NASMe) that was post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde per unit when it was alternately immersed in water at 4°C and 25°C. As shown in Figure 3, it became clear that the swelling ratio could be controlled by the degree of crosslinking.
[0070] (8) Evaluation of shape memory The shape memory property was evaluated for P(NAGAm-NASMe) that was post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde. P(NAGAm-NASMe) that was post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde was cut into a rod shape (θ0 = 180 degrees) with a thickness of 1 mm and a length of 30 x width of 2 (mm). The cut hydrogel was immersed in water at 25°C for 1 hour, then bent 180 degrees and immersed in water at 4°C for 1 hour to fix the shape. After fixing, the fixing force was removed from the gel, the angle (θ1) maintained at that time was measured, and the shape fixation rate (F) was calculated from the following formula.
[0071] Shape fixing percentage (F) (%) = {(θ0-θ1) / θ0} × 100
[0072] Thereafter, the sample was immersed in water at 25° C. for 1 hour, the angle (θ2) at which the shape was restored was measured, and the shape recovery rate (R) was calculated using the following formula.
[0073] Shape recovery percentage (R) (%) = (θ2 / θ1) × 100
[0074] Figure 4 shows the shape fixation rate (F) of P(NAGAm-NASMe) post-crosslinked with 1, 10, and 100 equivalents of glutaraldehyde per unit. As shown in Figure 4, the hydrogel of this example had excellent shape fixation rate.
[0075] (9) Evaluation of shape recovery rate The shape recovery rate was evaluated for P(NAGAm-NASMe) that was post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde. Figure 5 shows the shape recovery rate (R) of P(NAGAm-NASMe) that was post-crosslinked with 1, 10, and 100 equivalents of the crosslinking agent glutaraldehyde per unit. As shown in Figure 5, the hydrogel of this example had an excellent shape recovery rate.
[0076] (10) Post-crosslinking with hexamethylene diisocyanate (HDI) In the above-mentioned examples, the polymerized P(NAGAm-NASMe) was post-crosslinked with glutaraldehyde. However, the crosslinking agent capable of post-crosslinking the hydrogel of the present invention is not limited to glutaraldehyde, and post-crosslinking with, for example, hexamethylene diisocyanate (HDI) is also possible.
[0077] The solvent of P(NAGAm-NASMe) prepared at 4 wt% was replaced with acetonitrile, and then hexamethylene diisocyanate (HDI) (10 eq.) was added to the amount of P(NAGAm-NASMe) and reacted at 70°C for 8 hours. After that, the solvent was replaced with water again to make a hydrogel.
[0078] Dynamic viscoelasticity measurements were performed on P(NAGAm-NASMe) that was post-crosslinked with 10 equivalents of the crosslinking agent hexamethylene diisocyanate, and the storage modulus (G') at 6.3 rad / s was compared. The measurement conditions were 4°C and strain 1%. Figure 6 shows the storage modulus (G') of P(NAGAm-NASMe) that was post-crosslinked with 10 equivalents of hexamethylene diisocyanate per unit. As shown in Figure 6, it was revealed that the storage modulus (G') can be controlled before and after crosslinking.
[0079] (11) Post-crosslinking with ethylenediamine (EDA) In the above-mentioned examples, the polymerized P(NAGAm-NASMe) was post-crosslinked with glutaraldehyde. However, the crosslinking agent capable of post-crosslinking the hydrogel of the present invention is not limited to glutaraldehyde, and for example, P(NAGAm-NAG) can also be post-crosslinked with ethylenediamine (EDA).
[0080] Ethylenediamine (EDA) (10 eq.) and DMT-MM (25 eq.) (condensation agent) were added to 1 unit of P(NAGAm-NAG) in 0.05 M Tris-HCl buffer, and the mixture was reacted at 25°C for 24 hours and then thoroughly washed with Tris-HCl buffer.
[0081] Dynamic viscoelasticity measurements were performed on P(NAGAm-NAG) that was post-crosslinked with 10 equivalents of ethylenediamine (EDA), and the storage modulus (G') at 6.3 rad / s was compared. The measurement conditions were 4°C and 1% strain. Figure 7 shows the storage modulus (G') of P(NAGAm-NAG) that was post-crosslinked with 10 equivalents of ethylenediamine per unit. As shown in Figure 7, it was revealed that the storage modulus (G') can be controlled before and after crosslinking.
[0082] (12) Evaluation of self-repairing ability Water was added to the polymerized P(NAGAm-NASMe) powder to a concentration of 4 wt%, and the mixture was poured into a dumbbell-shaped mold. It was then dissolved in a microwave oven (approximately 90°C) and cooled to 4°C to gel in a dumbbell shape.
[0083] Fig. 8 is a photograph showing the self-repairing property of the hydrogel of the present invention. As shown in Fig. 8, when the center of a dumbbell-shaped hydrogel was cut, the cut parts were overlapped and left at 70°C for 30 minutes and then cooled, the cut parts were repaired and restored to their original shape.
[0084] Figure 9 compares the tensile stress of the hydrogel before and after repair. As shown in Figure 9, compared to the hydrogel before cutting, the hydrogel repaired after cutting showed a slight decrease in tensile stress, but still had a very high self-repairing ability. [Industrial Applicability]
[0085] It can be used for medical materials, engineering materials, cosmetics, quasi-drugs, hobby materials, etc.
Claims
1. A shape-memory hydrogel comprising a polymer matrix and water, The polymer matrix comprises a monomer represented by formula (1), 【Chemistry 1】 A shape-memory hydrogel (R 1 is hydrogen or a straight or branched alkyl group having 1 to 6 carbon atoms.
2. The shape-memory hydrogel (R) according to claim 1, characterized in that the polymer matrix is a copolymer represented by formula (2). 2 is hydrogen or a linear or branched alkyl group having 1 to 6 carbon atoms, X is a structure in which a substituted or unsubstituted hydroxy group, a substituted or unsubstituted amino group, a substituted or unsubstituted carboxy group, a substituted or unsubstituted thiol group, a substituted or unsubstituted aldehyde group, a cyano group, or an epoxy group is bonded directly or via a linker, a is 1 to 20, and n is a repeating unit defined by the molecular weight of the compound. 【Chemistry 2】
3. The shape-memory hydrogel according to claim 2 , wherein the linker includes an amide bond, an ether bond, an ester bond, a urethane bond, or a thioether bond.
4. The shape-memory hydrogel (R) according to claim 1, characterized in that the polymer matrix is a copolymer represented by formula (2). 2 is hydrogen or a linear or branched alkyl group having 1 to 6 carbon atoms, X represents -CONH-Q, -COO-Q, an alkylene group, or an arylene group, and Q represents CHR 3 C.O.R. 4 and R 3 is CH 2 OH, CH(OH)CH 3 , (CH 2 ) 4 N.H. 2 , C.H. 2 COOR 5 , (CH 2 ) 2 COOR 5 , C.H. 2 S.H., C.H. 2 CONH 2 and (CH 2 ) 2 CONH 2 R is selected from the group consisting of 5 is selected from the group consisting of H, an alkyl, aralkyl or aryl group having 1 to 9 carbon atoms; R 4 NH 2 OR 6 and R 6 is H, an alkyl, aralkyl or aryl group having 1 to 9 carbon atoms, a is 1 to 20, and n is a repeating unit defined by the molecular weight of the compound. 【Chemistry 3】
5. 2. The shape-memory hydrogel according to claim 1, wherein the ethylenically unsaturated monomer is a monomer containing an ethylenically unsaturated group selected from the group consisting of acryloyl, methacryloyl, vinyl, and combinations thereof.
6. The shape-memory hydrogel according to claim 1, characterized in that the ethylenically unsaturated monomer is any one of N-(meth)acryloylserine methyl ester, N-(meth)acryloylglycine, N-(meth)acryloylvaline, N-(meth)acryloyllysine methyl ester, N-(meth)acryloylcysteine methyl ester, N-(meth)acryloylglutamic acid methyl ester, N-(meth)acryloylaspartic acid methyl ester, (meth)acryloylglycine amide, (meth)acryloylasparagine amide, and (meth)acryloylglutamine amide.
7. The ethylenically unsaturated monomer is any one of acrylic acid, methacrylic acid, 2-carboxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, N-(2-hydroxyethyl)acrylamide, N-(2-aminoethyl)methacrylamide hydrochloride, maleic acid, monomethyl maleic acid, 2-carboxyethyl methacrylate, N,N' dimethylacrylamide, N,N' diethylacrylamide, butylcarbamoylethyl acrylate, itaconic acid, crotonic acid, fumaric acid, styrenesulfonic acid, vinylbenzoic acid, vinylphosphonic acid, sulfopropyl (meth)acrylate, and sulfatoethyl (meth)acrylate. The shape-memory hydrogel according to claim 1.
8. The shape-memory hydrogel according to claim 1 , wherein the copolymer forming the polymer matrix has an intermolecular cross-linked structure.
Citation Information
Patent Citations
Shape-memory hydrogel
JP7025749B2
Cited By
Hydrogel patch for gastric perforation repair and preparation method thereof
CN121378564A